2013
DOI: 10.1371/journal.pone.0065334
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Transfusion-Associated Graft-versus-Host Disease by Irradiation: Technical Aspect of a New Ferrous Sulphate Dosimetric System

Abstract: Irradiation of whole blood and blood components before transfusion is currently the only accepted method to prevent Transfusion-Associated Graft-Versus-Host-Disease (TA-GVHD). However, choosing the appropriate technique to determine the dosimetric parameters associated with blood irradiation remains an issue. We propose a dosimetric system based on the standard Fricke Xylenol Gel (FXG) dosimeter and an appropriate phantom. The modified dosimeter was previously calibrated using a 60Co teletherapy unit and its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Furthermore, only the canister central plane was considered in the analysis of the mean doses. Although they did not find a significant difference between the dosimeters, the results for relative final uncertainty are not described 6 . The Fricke solution dosimetry can be considered an alternative to TLD or FXG, due its low associated uncertainties, and lower costs, even when working with a primary level dosimeter.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, only the canister central plane was considered in the analysis of the mean doses. Although they did not find a significant difference between the dosimeters, the results for relative final uncertainty are not described 6 . The Fricke solution dosimetry can be considered an alternative to TLD or FXG, due its low associated uncertainties, and lower costs, even when working with a primary level dosimeter.…”
Section: Resultsmentioning
confidence: 91%
“…Studies already claim that the dose delivered to the entire blood bag must have at least 25 Gy. This recommendation takes into account changes in the recovery of transfused cells derived from irradiated bags, the erthrocyte, granulocyte and platelet functions, and changes in biochemistry 6,25 . The design of the developed phantom allowed the verification that the dose inside the canister is not uniformly distributed, because of this, some of the irradiated blood bags will not receive the recommended dose of 25 Gy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a measure of potential diagnostic performance, sensitivity and specificity were calculated: Sensitivity = ELISA positive samples/ S. scabiei infected samples × 100 %; Specificity = ELISA negatives samples/ S. scabiei non-infected samples × 100 % [ 27 , 28 ]. The cut-off value between negative and positive results was calculated as the average measurement of the mange negative animals plus three times the standard deviation [ 29 – 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, leukocytes should be non-irradiated. While irradiation helps to minimize the risk of GVHD [13] , Stehle Jr. et al and other studies showed that irradiation of donor leukocytes had a profound suppressive effect on the CKA and survival of irradiated compared to non-irradiated granulocytes [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%